SSRI Facilitated Crack Dancing. (11th April 2017) - Doobay, Ravi; Sun, Lili; Shah, Amish; Masuta, Pardeep; Shepherd, Zachary
Abstract : Choreoathetoid movement secondary to cocaine use is a well-documented phenomenon better known as "crack dancing." It consists of uncontrolled writhing movements secondary to excess dopamine from cocaine use. We present a 32-year-old male who had been using cocaine for many years and was recently started on paroxetine, a selective serotonin reuptake inhibitor (SSRI) for worsening depression four weeks before presentation. He had been doing cocaine every 2 weeks for the last three years and had never "crack danced" before this episode. The authors have conducted a thorough literature review and cited studies that suggest "crack dancing" is associated with excess dopamine. There has never been a documented case report of an SSRI being linked with "crack dancing." The authors propose that the excess dopaminergic effect of the SSRI lowered the dopamine threshold for "crack dancing." There is a communication with the Raphe Nucleus and the Substantia Nigra, which explains how the SSRI increases dopamine levels. This is the first documented case of an SSRI facilitating the "crack dance."